A response to Eski’s and Sergi’s ‘mafia-cation’. Confronting an ‘imagined’ narrative with empirical evidence - Soudijn, Melvin (Trends in organized crime, 2024)
Yarin Eski and Anna Sergi recently published an article in Trends in Organized Crime called ‘Ethnic profiling of organised crime? A tendency of mafia‑cation in the Netherlands’ Eski and Sergi (Trends Organ Crime, 1?20 2023). In their theoretical contribution, the authors claim that the policing of organised crime in the Netherlands amounts to ethnic profiling of minorities. However, the question of whether Dutch organised crime policies focus on ethnic minorities is in fact an empirical one. While Eski and Sergi claim the existence of an ‘ethnicised’ focus, the use of the phrase ‘theoretical’ is a rather ineffective attempt to cover up methodological weaknesses and a lack of empirical substantiation. Court records, records of the Public Prosecution Service, parliamentary documents, and academic research into organised crime provide not a shred of evidence of mafia-cation.